2017
DOI: 10.1097/hnp.0000000000000225
|View full text |Cite
|
Sign up to set email alerts
|

Flow in Nurses

Abstract: How does the experience of flow among nurses influences their health? This question is addressed on the basis of a model of flow, stress, burnout, and coping. The results indicate that promoting flow can be a way to enhance the health of ward nurses in a hospital work context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Positive and supportive work environments contribute to a higher degree of employee success (Schaufeli & Bakker, 2003). In addition, leadership is critical to empowering nurses to feel engaged in their work (Martínez-Zaragoza et al, 2017). Leadership behaviors are key to creating employees' positive responses to work; specifically, transformational leadership behaviors encourage greater work engagement (Lewis & Cunningham, 2016), as nurses feel more empowered and have ownership over the success of the workplace.…”
Section: Introductionmentioning
confidence: 99%
“…Positive and supportive work environments contribute to a higher degree of employee success (Schaufeli & Bakker, 2003). In addition, leadership is critical to empowering nurses to feel engaged in their work (Martínez-Zaragoza et al, 2017). Leadership behaviors are key to creating employees' positive responses to work; specifically, transformational leadership behaviors encourage greater work engagement (Lewis & Cunningham, 2016), as nurses feel more empowered and have ownership over the success of the workplace.…”
Section: Introductionmentioning
confidence: 99%
“…While nursing is a profession characterized by a high level of job demands in terms of tasks and relationships with suffering patients, it is also an engaging and motivating profession (Bringsén et al, 2011; Martínez-Zaragoza et al, 2017; Zito et al, 2019; Zito, Bakker et al, 2015). The nursing profession is subject to what Csikszentmihalyi (1997) called the “work paradox”: on the one hand, nurses report positive experiences of satisfaction and pleasure related to a high level of motivation; on the other hand, they report fatigue and a desire to quit their work.…”
Section: The Present Studymentioning
confidence: 99%
“…Nursing profession is attracting the attention of scholars because the health care sector is beset by problems, such as the growing demands of health and an aging workforce, increasing workloads, absenteeism or stress, and the resulting intention to leave the profession (Duhoux et al, 2017; Heinen et al, 2013; Martínez-Zaragoza et al, 2017; Pyrillis, 2013; Zito et al, 2013). Not surprisingly, these are some of the critical issues that can affect workers’ perceptions of well-being and enhance both psychological and physical distress among healthcare workers such as nurses (Chan et al, 2013; Zito et al, 2016; Zito, Colombo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study that investigated burnout in nurses, achieving flow states was found to positively influence health and the use of approach coping mechanisms (i.e. respectful confrontation, search for social support, and goal-oriented planning), thus indirectly decreasing burnout [11]. A recent randomized control trial by McGonagle et al [12 ▪▪ ] investigated burnout and wellness in primary care physicians who underwent coaching interventions.…”
Section: Flow In Literaturementioning
confidence: 99%